PENGARUH KARAKTERISTIK PERUSAHAAN DAN GOOD CORPORATE GOVERNANCE TERHADAP PENGUNGKAPAN SUSTAINABILITY REPORT - admin, Safitri B11112006 (Jurnal Manajemen Update, 2016)
This research aims to examine and analyze the effects of the characteristics Company and Good Corporate Governance on Sustainability Report Disclosure on companies listed in the Indonesia Stock Exchange and is also a participant in Indonesia Sustainability Report Awards for the period 2010-2014. Independent variables used in the Company Characteristics are Profitability,Firm Size and Firm Age whereas Good Corporate Governance Company while used a variable size of the Board of Commissioners and of the Audit Committee. The Dependent Variables used is Disclosure of Sustainability Report. The kind of this research is quantitative research. The research population includes companies listed on the Indonesia Stock Exchange once registered in Indonesia Sustainability Report Awards. Sample was collected by purposive sampling method. The data of the research population as many as 29 companies, and obtained a sample of 15 companies. The analysis technique used was multiple linear regression, used Â SPSS with the simultaneous test (Test F), and the partial test (t test). The results of the research showed that the size of the Audit Committee had a significant influence with a positive coefficient on the Disclosure of Sustainability Report, firm Size and firm Age had a significant influence with a negative coefficient on the Disclosure of Sustainability Report, while Profitability and size of the Board of Commissioners effect had no significant with a positive coefficient on the Disclosure of Sustainability Report. The ability of the five variables in explain the effect of the Sustainability Report Disclosure by 27.4% as show by the amount of adjusted R-square of 27.4% while the remaining 72.6% influenced by other factors not included in this research model Keywords: Characteristics of Companies, good corporate governance, profitability, firm size, firm age, size of the Board Commissioners, size of the Audit Committee, Disclosure Sustainability Report.